2012
DOI: 10.1016/j.neubiorev.2012.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Learning from experience: Event-related potential correlates of reward processing, neural adaptation, and behavioral choice

Abstract: To behave adaptively, we must learn from the consequences of our actions. Studies using event-related potentials (ERPs) have been informative with respect to the question of how such learning occurs. These studies have revealed a frontocentral negativity termed the feedback-related negativity (FRN) that appears after negative feedback. According to one prominent theory, the FRN tracks the difference between the values of actual and expected outcomes, or reward prediction errors. As such, the FRN provides a too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

57
465
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 457 publications
(541 citation statements)
references
References 195 publications
57
465
10
Order By: Relevance
“…Previous studies focusing on the age-related alterations in feedback evaluation processes found both differences and similarities in the morphology of the FRN and related P3 between young and elderly participants [35,36,39,[56][57][58][59][60]. The finding of the present study that the magnitude of the FRN component for the negative feedback (the balloon burst itself) did not differ between the two age groups suggests that the rapid processing of negative feedback valence was equally functional in both groups emphasizing the intact sensitivity to negative events in the elderly.…”
Section: Interpretation Of the Electrophysiological Resultsmentioning
confidence: 98%
“…Previous studies focusing on the age-related alterations in feedback evaluation processes found both differences and similarities in the morphology of the FRN and related P3 between young and elderly participants [35,36,39,[56][57][58][59][60]. The finding of the present study that the magnitude of the FRN component for the negative feedback (the balloon burst itself) did not differ between the two age groups suggests that the rapid processing of negative feedback valence was equally functional in both groups emphasizing the intact sensitivity to negative events in the elderly.…”
Section: Interpretation Of the Electrophysiological Resultsmentioning
confidence: 98%
“…Neural responses to negative or unexpected action outcomes have been the main target of research seeking to understand neural mechanisms of adaptive behavior in humans (Luft, 2014; Walsh & Anderson, 2012; Weinberg, Dieterich, & Riesel, 2014). Electroencephalographic (EEG) and magnetoencephalographic (MEG) studies have identified evoked responses elicited by errors in motor tasks (error‐related negativity, ERN, Ne) (Falkenstein, Hohnsbein, & Hoormann, 1995; Holroyd & Coles, 2002; Keil, Weisz, Paul‐Jordanov, & Wienbruch, 2010) as well as by external feedback (Feedback‐Related Negativity, FRN) (Doñamayor, Marco‐Pallarés, Heldmann, Schoenfeld, & Münte, 2011; Doñamayor, Schoenfeld, & Münte, 2012b; Gehring & Willoughby, 2002; Miltner, Braun, & Coles, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The FRN is a medial frontal negativity that appears approximately 200–300 ms following feedback presentation, which is larger following monetary losses than gains (Gehring & Willoughby, 2002; Walsh & Anderson, 2012). Holroyd and Coles (2002) first proposed that the FRN represents a reward prediction error “corresponding to the difference between the amount of reward obtained and the prior expected value of the reward,” indicating that the FRN amplitude should encode both valence and magnitude (see also Hajihosseini & Holroyd, 2013; Holroyd, Larsen, & Cohen, 2004).…”
Section: Introductionmentioning
confidence: 99%